Manifestaciones bucales en pacientes pediátricos bajo terapia oncológica y su protocolo de higiene oral. Revisión de la literatura (2020)
Childhood cancer is rare and only represents between 0.5% and 3% of malignant neoplasms in the world. Objective: To determine, according to a literature review, the most frequent oral manifestations in pediatric patients under cancer treatment. Materials and methods: The present study was carried out through a bibliographic review of different investigations of scientific articles that were found in the platforms of Pubmed, Latindex, Cochrane and Lilacs related to oral manifestations in children under cancer treatment and preventive dental care protocols, published in 1998 Until 2019, 52 articles were selected from the Pubmed, Latindex, Cochrane and Lilacs databases